2017
DOI: 10.1007/s00540-017-2424-1
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of pharmacokinetic models of intravenous dexmedetomidine in sedated patients under spinal anesthesia

Abstract: Hannivoort et al.'s pharmacokinetic model, constructed with a dataset obtained from healthy volunteers, can predict dexmedetomidine concentrations best during continuous infusion under spinal anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…To date, 11 dexmedetomidine pharmacokinetic (PK) models for adults have been published since Dyck et al demonstrated the first PK model in 1993 . Obara et al evaluated the predictive ability of nine PK models of dexmedetomidine and found that the model of Hannivoort et al most accurately predicted the dexmedetomidine plasma concentration in patients undergoing spinal anaesthesia. Recently, Colin et al reported a pharmacokinetic‐pharmacodynamic (PKPD) model for sedation scale and bispectral index (BIS) that was developed in the same subjects used in Hannivoort's PK model .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…To date, 11 dexmedetomidine pharmacokinetic (PK) models for adults have been published since Dyck et al demonstrated the first PK model in 1993 . Obara et al evaluated the predictive ability of nine PK models of dexmedetomidine and found that the model of Hannivoort et al most accurately predicted the dexmedetomidine plasma concentration in patients undergoing spinal anaesthesia. Recently, Colin et al reported a pharmacokinetic‐pharmacodynamic (PKPD) model for sedation scale and bispectral index (BIS) that was developed in the same subjects used in Hannivoort's PK model .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…To date, 11 dexmedetomidine pharmacokinetic (PK) models for adults have been published since Dyck et al 4 demonstrated the first PK model in 1993. 5 Obara et al 6 that was developed in the same subjects used in Hannivoort's PK model. 7 This PKPD model enables prediction of the dexmedetomidine effect-site concentration (Ce) and target-controlled infusion (TCI).…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…38 Absolute values of the performance criteria as published by Varvel et al 33 have to be carefully interpreted in the context of this study, using supraclinical concentrations of dexmedetomidine and taking into account possible drug interactions. Using much lower concentrations of dexmedetomidine, Obara et al 39 validated the Hannivoort model on their data and found also better performance of the Hannivoort model with a median absolute performance error of 18% and median performance error of 5.6%. When evaluating the performance of the Hannivoort model in the lower (clinical) concentration range, we concluded that no adjustments to the model need to be made for use in clinical practice as long as targets do not exceed 3 ng/ml.…”
Section: Interaction Of Remifentanil and Dexmedetomidinementioning
confidence: 99%
“…Hannivoort found that a three-compartment structural model described the pharmacokinetic data best, but also found that allometric scaling of volumes and clearances resulted in a better fit (Table 3). The Hannivoort PK model performed better than previously published PK models in an initial prospective validation study, where patients received dexmedetomidine during spinal anaesthesia [27]. However, in a subsequent interaction study by Weerink et al, in which healthy volunteers received dexmedetomidine and remifentanil, the Hannivoort PK model performed well only up until targets < 3 ng mL −1 ; but for higher concentrations (which are rarely necessary in clinical practice) non-linear kinetics were suspected and confirmed by Alvarez-Jiminez et al in a closer analysis of both the Hannivoort and Weerink data [35][36][37].…”
Section: The Hannivoort-colin Pkpd Model For Dexmedetomidinementioning
confidence: 84%